Um esquema geral para a discussão do movimento de materiais para as células vivas e tecidos - Broyer, T. C.; Malavolta, E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
A generalized comprehensive scheme concerning the movement of materials into living cells and tissues is presented. It is designed for use by investigators and teachers who, is assumed, have a previous knowledge of the subject as well as familiarity with previously published literature on the subject. Footnotes to figure 2 X = a constituent component material, arising from extermal sources or through metabolism, capable of migration under favorable conditions. e, i, ec, ic, mc = subscripts indicating location. oC = oxidized cytoplasmic constituents specifically concerned in unidirectional (here invardly directed), diffetial translocation of a particular material X. rC = reduced cytoplasmic constituents specifically concerned. XF = specific free energy (2) of a constituent component in in external or internal phases or in cytoplasm. D = diffusion (4). EA = exchange adsorption (4). MA= metabolic accumulation (4), CI = differentially characteristic cytoplasmic interaction (4) between oC and X, determined by the genetic constitution of the biological species. ▬▬▬>= migration, where permeability to the material involved is relatively high; and ->, where relatively low.